Spatial assessment of the potential of renewable energy: The case of Ecuador - Cevallos Sierra, Jaime (2018)
Although renewable energy represents a large share of the electric energy generation sources in Latin America, non-conventional sources such as solar or wind energies have not represented a big share of their electric energy systems. The first step to promote the use of these sources in the region is identifying the potential of each energy source, task that can be estimated with the use of spatial tools such as Geographic Information Systems (GIS). This study has reviewed a large list of GIS publications to select a methodology to identify suitable areas for the development of non-conventional renewable energy projects (REP), in order to estimate the maximum energy these technologies could contribute to a national electric energy system, and its applied to the Republic of Ecuador. By using GIS, it is sought to identify the sites where potential renewable energy plants could be located, and initially recommends geographic locations for the installation of measuring towers of solar and wind resources, in order to obtain more detailed information on their behavior. As a result, the areas with higher potential for the development of REP have been identified, and classified in spatial layers according its technology and location. These results show that solar PV is the technology with most suitable areas in the country and demonstrate particularly large potential in two regions: the Andes cordillera and Insular region, especially in the provinces of Loja, Pichincha and the Galapagos islands.